Teori dan metodologi ilmu sosial dan antropologi dalam dinamika masyarakat dan kebudayaan - Pratama, Wildan (Maliki Interdisciplinary Journal, 2025)
Sociology and anthropology are two branches of social science that study humans, social behavior, and culture in the context of society. Both disciplines have a significant role in understanding the social interactions and cultural dynamics that shape human collective life. This research aims to explore the meaning, scope, purpose, basic concepts, and relationship between sociology and anthropology, in the hope of providing a deeper insight into the contribution of these two fields in the study of society. The method applied is a literature study to analyze various written sources. The research findings show that although sociology and anthropology have different goals, they complement each other in understanding social and cultural phenomena, especially in the face of social change in the modern era. Dynamics refer to the behavior of individuals who can directly influence others in reciprocal interactions. In addition, dynamics are also one of the elements of societal changes that take place over time. Interaction and interdependence between group members are known as dynamics.